2017
DOI: 10.1515/biolog-2017-0173
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial properties of 6-pentyl-α-pyrone produced by endophytic strains of Trichoderma koningii and its effect on aflatoxin B1 production

Abstract: A total of 60 endophytic fungal strains were isolated and screened for their producing-ability of 6-pentyl-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Isotopic labeling experiments in T. atroviride in the early 1990s suggested the oxidation of linoleic acid by a lipoxygenase as a first step in the biosynthesis of 6-PP, one of T. atroviride ’s main secondary metabolites with antifungal and plant growth promoting properties ( Scarselletti and Faull, 1994 ; Vinale et al, 2008 ; Garnica-Vergara et al, 2016 ; Ismaiel and Ali, 2017 ). In this study, we showed, however, that 6-PP biosynthesis in T. atroviride is not affected by deletion of the single lipoxygenase-encoding gene lox1 encoded in its genome.…”
Section: Discussionmentioning
confidence: 99%
“…Isotopic labeling experiments in T. atroviride in the early 1990s suggested the oxidation of linoleic acid by a lipoxygenase as a first step in the biosynthesis of 6-PP, one of T. atroviride ’s main secondary metabolites with antifungal and plant growth promoting properties ( Scarselletti and Faull, 1994 ; Vinale et al, 2008 ; Garnica-Vergara et al, 2016 ; Ismaiel and Ali, 2017 ). In this study, we showed, however, that 6-PP biosynthesis in T. atroviride is not affected by deletion of the single lipoxygenase-encoding gene lox1 encoded in its genome.…”
Section: Discussionmentioning
confidence: 99%
“…6PP produced by Trichoderma spp. promotes plant growth, shows activity against pathogens, and regulates root architecture by inhibiting primary root growth and inducing lateral root formation (Garnica‐Vergara et al., 2016; Ismaiel & Ali, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…6PP produced by Trichoderma spp. promotes plant growth, shows activity against pathogens, and regulates root architecture by inhibiting primary root growth and inducing lateral root formation (Garnica-Vergara et al, 2016;Ismaiel & Ali, 2017). The UFRAB01 strain of B. amyloliquefaciens used in our study was evaluated on oil palm plants in the laboratory and was found to be beneficial to produce indole acetic acid (IAA), 1-carboxylic acid-1-aminocyclopropane (ACC), and abscisic acid (ABA) (Lima et al, 2020).…”
Section: Benefits Of Soybean Co-inoculationmentioning
confidence: 99%
“…They were morphologically identified and deposited in the Assiut University Mycological Center (AUMC, http://www.aun . edu.eg/aumc/aumc.htm) with accession numbers: AUMC11519, AUMC11520, AUMC11521, and AUMC11522, respectively (Ismaiel and Ali 2017 ).…”
Section: Methodsmentioning
confidence: 99%